2007
DOI: 10.1109/iembs.2007.4352760
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Novel ECG Signal Processing on Quantification of Transient Ischemia and Baseline Wander Suppression

Abstract: The performance assessment of a novel ECG signal processing technology in Fidelity 100 (test) and four modern ECG systems (controls) was conducted. A quantitative evaluation for one control and a test system was done by simultaneous recordings on 54 patients undergoing percutaneous coronary intervention (PCI) and on a biological reference signal from an ECG simulator. A qualitative performance of baseline wander suppression was done on all five systems. The results showed that the Fidelity 100 system provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…However, larger studies that investigate patient populations with several different pathophysiologies are required to convince clinicians to adopt another patient monitoring technology in their workflows. Fidelity 100 is an FDA 510 (k) approved wireless ECG monitor developed by Signalife (Studio City, CA, USA), which was evaluated in real-time in 54 patients undergoing percutaneous coronary intervention [83]. Although these monitors come with different settings applicable for use in different types of CCUs, validation studies on population data from all application domains are not found.…”
Section: E Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, larger studies that investigate patient populations with several different pathophysiologies are required to convince clinicians to adopt another patient monitoring technology in their workflows. Fidelity 100 is an FDA 510 (k) approved wireless ECG monitor developed by Signalife (Studio City, CA, USA), which was evaluated in real-time in 54 patients undergoing percutaneous coronary intervention [83]. Although these monitors come with different settings applicable for use in different types of CCUs, validation studies on population data from all application domains are not found.…”
Section: E Clinical Evaluationmentioning
confidence: 99%
“…Theoretically, a missed event or a false alarm are caused by artifacts of various types; for example, motion artifact and power line or optical noise induced in an attached or detached sensor. Studies that collected real-time annotated data or video monitored data, such as [27,31,36,[80][81][82][83][84][85][86] among others, can utilise the same data sets to develop and validate SQIs. Compatible SQIs can be used to compare performance of different AD algorithms and OEM monitors.…”
Section: E Clinical Evaluationmentioning
confidence: 99%
“…However, the same event could be very important clinically and crucial that it not be missed even once. Theoretically, a missed event or a false alarm may be caused by artifacts of various types; for example, motion artifact and power line or optical noise induced in an attached or detached sensor.Studies that collected real-time annotated data or video monitored data, such as[67,70,74,75,121,124,129,136,170,183] among others, can utilise the same data sets to develop and validate SQI. Compatible SQI can be used to compare performance of different AD algorithms and OEM monitors.…”
mentioning
confidence: 99%
“…Examples include work done by Portet et al[135] that contributed towards the BabyTalk project in[184], the author's own work in[132] that serves as preliminary research in Artemis[31], and work done by Seely et al[25,[185][186][187] that formed part of the CIMVA tool (this project is now closed; it was previously funded by TMS Inc., Ottawa, Canada). Research in which data were both annotated and evaluated in real-time include[126,129,170]; however, none of these algorithms were put into actual clinical practice. Correlating the results from Themes V and VI also identifies the research in which data were annotated and evaluated in real-time and the work was commercialized thus reaching clinical implementation.…”
mentioning
confidence: 99%